Lithium metal composite negative electrode material, preparation method and battery thereof
By setting up a lithium-philic transition layer and a lithium metal layer on the polymer base film, the problem of insufficient mechanical strength of the lithium metal negative electrode material is solved, and a lithium metal composite negative electrode material with high toughness, high strength and low weight is achieved, improving the energy density and safety performance of the battery.
Patent Information
- Application Number
- CN202510108106.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
AI Technical Summary
The insufficient mechanical strength of lithium metal in lithium-ion batteries leads to poor compatibility, degradation of performance and low safety, especially when volume changes, brittle fracture is prone to occur.
A polymer base film is used as the substrate, and a lithium-philic transition layer is provided on the upper and lower surfaces of it, and a lithium metal layer is provided outside the transition layer. A lithium-philic transition layer and a copper layer are formed through magnetron sputtering process to enhance interface adhesion and conductivity.
The mechanical properties and electrical conductivity of lithium metal negative electrode materials are improved, the weight of composite materials is reduced, the energy density and safety performance of the battery are improved, and the overhang fracture of the electrode sheet is avoided.
Smart Images

Figure CN119905521A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular, relates to a lithium metal composite negative electrode material, a preparation method and a battery thereof. Background Art
[0002] In the field of lithium-ion batteries, lithium metal is regarded as an ideal negative electrode material due to its extremely high theoretical specific capacity (3860mAh / g). However, lithium metal has a significant problem of insufficient mechanical strength in practical applications, which not only limits its compatibility in the battery manufacturing process, but also affects the overall performance and safety of the battery. In order to address this challenge, the industry has adopted a variety of methods to enhance the mechanical properties of lithium metal, among which the roller pressing method has attracted attention because it can effectively improve the support compatibility of the battery cell. Although the roller pressing method significantly improves the mechanical strength of lithium metal by combining copper foil with metallic lithium to form a lithium-copper composite strip, this method introduces a heavier copper substrate material, which sacrifices the energy density of the battery to a certain extent. The weight of the copper substrate material increases the inactive mass of the battery, thereby reducing the energy density of the battery, which is an issue that cannot be ignored for modern battery technology that pursues high energy density. Moreover, the toughness of the copper-lithium composite negative electrode is relatively low and the safety is low. During the charge and discharge process, the volume change of the lithium metal negative electrode material causes the edge of the pole piece to be subjected to large mechanical stress, which includes extrusion and shear force. The action of these forces may cause fractures at the edge of the pole piece, especially in traditional copper-lithium composite strips. Due to their material properties, high-strength, low-toughness materials are more likely to fracture when subjected to cyclic stress. This phenomenon is called "overhang" fracture. Although traditional copper-lithium composite strips can provide the necessary mechanical support, their high-strength, low-toughness characteristics are inadequate when faced with the volume changes of lithium metal negative electrode materials. When subjected to repeated mechanical stress, this material is prone to brittle fracture, resulting in reduced battery performance and shortened cycle life. Therefore, it is urgent to develop a lithium metal composite negative electrode material with high toughness, high strength and light weight. Summary of the invention
[0003] In order to improve the mechanical properties of lithium metal negative electrode materials in the prior art, the present invention provides a lithium metal composite negative electrode material comprising: a polymer base film, a lithium-philic transition layer is respectively arranged on the upper and lower surfaces of the polymer base film, and a lithium metal layer is arranged outside the lithium-philic over-plating layer.
[0004] Furthermore, the lithium-philic overplating layer is arranged in the middle area of the upper and lower surfaces of the polymer base film, and the ends of the upper and lower surfaces of the polymer base film are arranged as copper layers.
[0005] Further, the material of the lithium-philic transition layer is one or more of aluminum oxide, copper oxide, nickel oxide, and cobalt oxide. Further, the material of the polymer base film is one or more of polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride, and polyimide.
[0006] Furthermore, the thickness of the lithium-philic transition layer material is 0.01-1 μm.
[0007] Furthermore, the thickness of the polymer base film is 2-6 μm.
[0008] Another aspect of the present invention provides a method for preparing the above-mentioned lithium metal composite negative electrode material, wherein the lithium-philic transition layer is composited onto the polymer base film by a sputtering process.
[0009] Furthermore, the method for the lithium metal composite negative electrode material comprises the following steps: S1: using a metal element as a target material, and using a magnetron sputtering process in an oxidizing gas atmosphere to sputter and deposit the lithium-philic transition layer in the middle area of the upper and lower surfaces of the polymer base film; S2. Using a copper element as a target material, and continuing to use a magnetron sputtering process in an inert gas atmosphere to deposit the copper layer in the end areas of the upper and lower surfaces of the polymer base film to form a composite current collector; S3: rolling a lithium strip on the surface of the composite current collector to form the lithium metal composite negative electrode material.
[0010] Another aspect of the present invention provides a battery comprising the above-mentioned lithium metal composite negative electrode material.
[0011] The lithium-philic transition layer of the lithium metal composite negative electrode material of the present invention enhances the interfacial adhesion between the polymer base film and the metallic lithium, achieves efficient bonding of the metallic lithium with the composite substrate, and improves the conductivity; at the same time, the polymer base layer solves the problem of fracture of the metallic lithium negative electrode that is prone to occur during the production of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0013] Figure 1 It is a schematic structural diagram of the lithium metal composite material of the present invention. DETAILED DESCRIPTION
[0014] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0015] 1. Preparation of negative electrode materials
[0016] Example 1
[0017] S1. Place a PP film with a thickness of 4.5 μm in a magnetron sputtering machine, use an aluminum target (purity 99.9%) as the target material, set the target power to 6 kW, use oxygen as the gas source, adjust the gas flow rate to the gas pressure in the cabin to 0.1 Pa, and perform magnetron sputtering treatment on the middle area of the upper and lower surfaces of the PP film for 60 seconds to control the formation of an aluminum oxide layer with a thickness of 1 μm in the middle area of the upper and lower surfaces of the PP film.
[0018] S2. Then, a copper target (purity 99.9%) is used as the target material, the target power is set to 6 kW, argon is used as the gas source, the gas flow rate is adjusted to the gas pressure in the chamber to be 0.1 Pa, and the ends of the upper and lower surfaces of the PP film (except the middle area in step S1) are magnetron sputtered for 60 seconds to form a copper layer with a thickness of 1 μm at the ends of the upper and lower surfaces of the PP film, thereby obtaining a composite current collector with a thickness of 6.5 μm.
[0019] S3. In a dry environment, roll-press a lithium strip on the middle area of the upper and lower surfaces of the composite current collector obtained in step S2. In this step, the rolling pressure is set to 5 tons, the rolling temperature is 25°C, the rolling speed is 3m / min, and the thickness of the lithium strip is 20μm, thereby obtaining an ultra-light composite lithium metal negative electrode material.
[0020] Through the above steps, a Figure 1 The lithium metal composite negative electrode material shown; the upper and lower surfaces of the polymer base film 1 are respectively provided with a lithium-philic transition layer 2, and a lithium metal layer 4 is provided outside the lithium-philic over-plating layer 2. The lithium-philic over-plating layer 2 is only provided in the middle area of the upper and lower surfaces of the polymer base film 1, and the ends of the upper and lower surfaces of the polymer base film are provided with a copper layer 3, and the portion where the copper layer 3 is located can be used as the battery tab later. The material of the polymer base film is one or more of polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride and polyimide. The thickness of the lithium-philic transition layer 2 is preferably set at 0.01-1μm; the thickness of the polymer base film 1 is preferably 2-6μm, and the material of the polymer base film 2 can be set to one or more of polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride and polyimide.
[0021] Example 2
[0022] This embodiment is basically the same as the embodiment 1, except that in step S1, a copper target (purity 99.9%) is used as the target material to control the formation of a copper oxide layer with a thickness of 1 μm in the middle area between the upper and lower surfaces of the PP film.
[0023] Example 3
[0024] This embodiment is basically the same as the embodiment 1, except that in step S1, a nickel target (purity 99.9%) is used as the target material to control the formation of a nickel oxide layer with a thickness of 1 μm in the middle area between the upper and lower surfaces of the PP film.
[0025] Example 4
[0026] This embodiment is basically the same as the embodiment 1, except that in step S1, a cobalt target (purity 99.9%) is used as the target material to control the formation of a cobalt oxide layer with a thickness of 1 μm in the middle area between the upper and lower surfaces of the PP film.
[0027] Comparative Example 1
[0028] A 4.5 μm PP film is used as a base film, and a 1 μm copper layer is plated on the upper and lower surfaces of the base film respectively to form a composite copper foil; in a dry environment, a lithium strip is rolled on the composite copper foil to obtain a composite lithium metal negative electrode material.
[0029] Comparative Example 2
[0030] In a dry environment, a 20μm lithium tape was rolled onto a 6μm thick copper foil to produce a copper-lithium composite tape.
[0031] 2. Test the tensile strength and surface density of the negative electrode material
[0032] The tensile strength and surface density of the negative electrode materials obtained in the above Examples 1-4 and the composite lithium metal negative electrode materials or copper-lithium composite tapes in the comparative examples were tested;
[0033] 2.1 Tensile strength: It is characterized by testing the maximum stress that the negative electrode material can withstand during the stretching process, that is, the maximum stress value reached by the negative electrode material before it breaks. The calculation formula is: σb = Fb / So, where Fb is the maximum force that the negative electrode material withstands when it is broken, and So is the original cross-sectional area of the negative electrode material; the greater the tensile strength of the negative electrode material, the more effectively it can improve the problem of insufficient mechanical properties of the lithium metal negative electrode.
[0034] 2.2 Surface density: The mass of the negative electrode material per unit area is measured by the weight method. Surface density is used to illustrate the change in the mass of the negative electrode material, which can indirectly represent the change in the battery energy density. The higher the surface density of the negative electrode material, the lower the battery energy density. 3. Assemble the negative electrode material into a battery and observe the battery overhang and needle penetration rate
[0035] The negative electrode obtained in all the above embodiments and comparative examples is used as the negative electrode of the battery; for the positive electrode, the positive electrode current collector is aluminum foil (12μm), the positive electrode active material is lithium nickel cobalt manganese oxide, and the positive electrode active material layer includes lithium nickel cobalt manganese oxide, conductive carbon (Super P), carbon nanotubes, and polyvinylidene fluoride, and the mass ratio of the four is: 96:1.6:0.7:1.7; for the electrolyte, the electrolyte is lithium bistrifluoromethanesulfonyl imide (LiTFSI) and lithium nitrate (LiNO3), the content is 1mol·L-1, 2wt% respectively, and the electrolyte is 1,2-dimethoxymethane (DME) and 1,3-dioxolane (DOL), and the volume ratio of the two is 1:1. For the diaphragm, a polypropylene diaphragm (thickness is 20μm) is used; the above materials are used to assemble the battery according to the conventional battery assembly process, and the battery capacity is 2.6Ah.
[0036] Puncture pass rate: A puncture test is used to verify the safety performance of the battery, as follows: 50 batteries are prepared using the negative electrode materials prepared by the above-mentioned all embodiments and comparative examples, and placed in a puncture test device, wherein the diameter of the steel needle is 6 mm, and the puncture speed is 25 mm / s. The battery passes if it does not explode, catch fire, or emit smoke during the puncture; otherwise, it fails. The number of batteries that pass and fail is recorded, and the battery puncture pass rate can be obtained, that is, the number of batteries that pass / the total number of batteries × 100%.
[0037] "Overhang" fracture condition: The "overhang" fracture condition is verified by observing the interface of the battery electrode after cycling, as follows: After 100 cycles of 1C / 1C charge and discharge of a battery assembled with negative electrode materials prepared by the methods of all the above embodiments and comparative examples, the battery is disassembled to observe the fracture condition of the electrode.
[0038] Record the results of the above experimental process in the following table
[0039]
[0040] From the table above we can see that:
[0041] A lithium metal composite negative electrode material prepared by the method of the present invention has significantly improved tensile strength compared to the copper-lithium composite tape of the comparative example, while maintaining a relatively low surface density. The lithium metal composite negative electrode material of the present invention includes a polymer base film and a lithium-philic transition layer (middle section) and a copper layer (two ends) arranged on both sides of the polymer base film. The lithium-philic transition layer can enhance the interfacial adhesion, and the coating thickness can be adjusted based on the type of lithium-philic layer and the sputtering process. The composite substrate realizes a sandwich structure through a local sputtering process. The polymer base film of the lithium metal composite negative electrode material of the present invention has a high elongation, which effectively improves the problem of insufficient mechanical properties of the lithium metal negative electrode; and this design significantly reduces the weight of the composite lithium tape, thereby improving the energy density of the battery core; the copper layers at both ends of the lithium metal composite negative electrode material of the present invention are used to prepare the battery's pole ears to bear the conductive effect, and have higher conductivity than the lithium-philic layer at the middle end. Therefore, in the middle lithium-philic layer, the structural design of the conductive layer at both ends can improve the conductivity of the battery. At the same time, the high strength and high toughness characteristics of the polymer substrate not only improve the compatibility of the battery cell manufacturing process, but also effectively avoid the problem of overhang fracture of the pole piece caused by high shear force during long-term cyclic use of the battery cell. Therefore, the needle penetration rate of the battery prepared by the lithium metal composite negative electrode material of the present invention is also greatly improved compared with the copper-lithium negative electrode battery, and the pole piece does not have "overhang" fracture after cycling, which significantly improves the safety performance of the lithium metal battery and prevents the occurrence of thermal runaway.
[0042] It is only a preferred embodiment of the invention and is not intended to limit the invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the invention should be included in the protection scope of the invention.
Claims
1. A lithium metal composite negative electrode material, characterized in that: include: The polymer base film has lithium-philic transition layers arranged on the upper and lower surfaces of the polymer base film respectively, and a lithium metal layer is arranged outside the lithium-philic over-plating layer.
2. The lithium metal composite negative electrode material according to claim 1, characterized in that The lithium-philic overplating layer is arranged in the middle area of the upper and lower surfaces of the polymer base film, and the ends of the upper and lower surfaces of the polymer base film are arranged as copper layers.
3. The lithium metal composite negative electrode material according to claim 2, characterized in that The material of the lithium-philic transition layer is one or more of aluminum oxide, copper oxide, nickel oxide, and cobalt oxide.
4. The lithium metal composite negative electrode material according to claim 2, characterized in that The material of the polymer base film is one or more of polyethylene terephthalate, polypropylene, polyethylene, polyvinyl chloride and polyimide.
5. The lithium metal composite negative electrode material according to claim 2, characterized in that: The thickness of the lithium-philic transition layer material is 0.01-1 μm.
6. The lithium metal composite negative electrode material according to claim 2, characterized in that: The thickness of the polymer base film is 2-6 μm.
7. A method for preparing the lithium metal composite negative electrode material according to any one of claims 1 to 6, characterized in that: The lithium-philic transition layer is compounded onto the polymer base film through a sputtering process.
8. The method for preparing a lithium metal composite negative electrode material according to claim 7, characterized in that: The method for preparing the lithium metal composite negative electrode material comprises the following steps: S1: using a metal element as a target, and using a magnetron sputtering process in an oxidizing gas atmosphere to sputter and deposit the lithium-philic transition layer in the middle area of the upper and lower surfaces of the polymer base film; S2. Using a copper element as a target, and continuing to use a magnetron sputtering process in an inert gas atmosphere to deposit the copper layer in the end areas of the upper and lower surfaces of the polymer base film to form a composite current collector; S3: rolling a lithium strip on the surface of the composite current collector to form the lithium metal composite negative electrode material.
9. A battery, characterized in that: The invention comprises a lithium metal composite negative electrode material as claimed in any one of claims 1 to 6.